Basic Principles and Clinical Applications of Magnetic Resonance Spectroscopy in Neuroradiology. Issue 1 (January 2016) - Ulmer, Stephan; Backens, Martin; Ahlhelm, Frank J.
Abstract : Abstract: Magnetic resonance spectroscopy is a powerful tool to assist daily clinical diagnostics. This review is intended to give an overview on basic principles of the technology, discuss some of its technical aspects, and present typical applications in daily clinical routine in neuroradiology.